2011
DOI: 10.1165/rcmb.2010-0004oc
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Macrophage Migration Inhibitory Factor and Eotaxin in Allergic Eosinophil Activation Forms Leukotriene C4–Synthesizing Lipid Bodies

Abstract: Recent studies have demonstrated an essential and nonredundant role for macrophage migration inhibitory factor (MIF) in asthma pathogenesis. Here we investigate the mechanisms involved in MIF-induced eosinophil activation. By using a model of allergic pulmonary inflammation, we observed that allergen challenge-elicited eosinophil influx, lipid body (also known as lipid droplets) biogenesis, and leukotriene (LT) C₄ synthesis are markedly reduced in Mif(-/-) compared with wild-type mice. Likewise, in vivo admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
1
24
1
Order By: Relevance
“…Nevertheless, in addition to the well-established Th2 background, these molecules apparently were not modulated by MIF, found in remarkably increased amounts in EoE samples. Although MIF has been shown to induce IL-5, IL-13 and eotaxin-3 in the lungs of allergic mice and eotaxin-3 by human eosinophils 15,17 , we also observed that MIF constitutes a critical survival factor for eosinophils, regardless of IL-5 or IL-13 levels 16 . Therefore, in this study we hypothesize that MIF may act in a relative independence of IL-5, IL-13, or eotaxin-3, through its effects on eosinophil recruitment and survival, suggesting a role for MIF as a key component of both Th2 and innate immune response circuits involved in the control of inflammation in EoE.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Nevertheless, in addition to the well-established Th2 background, these molecules apparently were not modulated by MIF, found in remarkably increased amounts in EoE samples. Although MIF has been shown to induce IL-5, IL-13 and eotaxin-3 in the lungs of allergic mice and eotaxin-3 by human eosinophils 15,17 , we also observed that MIF constitutes a critical survival factor for eosinophils, regardless of IL-5 or IL-13 levels 16 . Therefore, in this study we hypothesize that MIF may act in a relative independence of IL-5, IL-13, or eotaxin-3, through its effects on eosinophil recruitment and survival, suggesting a role for MIF as a key component of both Th2 and innate immune response circuits involved in the control of inflammation in EoE.…”
Section: Discussioncontrasting
confidence: 56%
“…Considering that in this study MIF was present mostly in eosinophils within the esophageal mucosa, it is conceivable that MIF may not constitute a primary trigger in EoE, but still emerges as a key element in the effector arm of EoE associated inflammation. Because of the ability of eosinophils to produce MIF 13,17 , it is also likely that effects observed in vivo might be a result of an autocrine/paracrine action of MIF released by eosinophil precursors in EoE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel correlation between fatigue intensification and eosinophil counts found in this study may be attributable to the increased concentrations of MIF, which has been shown to induce eosinophil infiltration and activation 47, 48 . Interestingly, eosinophils are a major source of cytokines and have been shown to release up to 35 different cytokines 49 .…”
Section: Discussionmentioning
confidence: 61%
“…LDs biogenesis is well documented both in vitro and in vivo in response to inflammatory stimuli and diseases (reviewed in [1, 2, 15]). For instance, increased LDs numbers are observed during acute respiratory distress syndrome [16] and allergic inflammation [17] in humans. Interestingly, eosinophils from patients with hypereosinophlic syndrome (HES) are naturally activated and show both increased numbers of LDs and enhanced leukotriene C 4 (LTC 4 ) production [18, 19].…”
Section: Lds As Critical Organelles Of Leukocytesmentioning
confidence: 99%